Digital media management training for more advanced village development in Desa Taringgul Tonggoh, Kec. Wanayasa - Wijaya, Adi; Rizky, Muhamad; Ghaida, Regina; Erawan, Bambang (Universitas Pendidikan Indonesia, 2023)
The Wanayasa area is one of the areas in Purwakarta that has abundant natural resources, creative and innovative human resources, and also has the potential for developing villages, one of which is Taringgul Tonggoh Village which has won 3rd place in the Java Province Village and Subdistrict Competition, west in 2023. The Village Government is trying to develop lagging aspects by developing digital media management to maintain what has been achieved. Therefore, the service program in the form of Real Work Lectures (KKN) created in this paper aims to educate the Village Government by conducting Digital Media Management Training for Village Development. This training aims to provide training so that Village Officials are proficient in operating Digital Media in Taringgul Tonggoh Village, including Instagram, Facebook, and the My Village Website. In digital media, village profiles are updated, village news adds village tourism, and completed village products (food and crafts) are in marketing features. After this program is implemented, village officials can create posters for design activities, social media posts in an organized manner, and appropriate captions for the posts. Village Officials gain insight into the village website and can manage it.